Comparing the Profiles of Raw and Cooked Donkey Meat by Metabonomics and Lipidomics Assessment - Li, Mengmeng; Ren, Wei; Chai, Wenqiong; Zhu, Mingxia; Man, Limin; Zhan, Yandong; Qin, Huaxiu; Sun, Mengqi; Liu, Jingjing; Zhang, Demin; Wang, Yonghui; Wang, Tianqi; et al. (Frontiers in Nutrition, 2022)
Heat cooking of meat gives it a specific taste and flavor which are favored by many consumers. While the characteristic taste components of chicken, duck, pig, and seafood have been studied, there is a lack of information about the molecular components that give donkey meat its unique taste. Here, the characterization profiles of raw donkey meat (RDM) and cooked donkey meat (CDM) meat by metabonomics and lipidomics. The results showed that a total of 186 metabolites belonging to 8 subclasses were identified in CDM and RDM, including carbohydrates (27.42%), amino acids (17.20%), lipids (13.44%), and nucleotides (9.14%). In total, 37 differential metabolites were identified between CDM and RDM. Among these, maltotriose, L-glutamate, and L-proline might predominantly contribute to the unique umami and sweet taste of donkey meat. Comprehensive biomarker screening detected 9 potential metabolite markers for the discrimination among RDM and CDM, including L-glutamate, gamma-aminobutyric acid, and butane-1,2,3,4-tetrol. Moreover, a total of 992 and 1,022 lipids belonging to 12 subclasses were identified in RDM and CDM, respectively, mainly including triglycerides (TGs and glycerophospholipids (GPs). Of these lipids, 116 were significantly different between CDM and RDM. The abundances of 61 TGs rich in saturated and monounsaturated fatty acids were retained in CDM, whereas the abundances of 37 GPs rich in polyunsaturated fatty acids were reduced, suggesting that TGs and GPs might be the predominant lipids for binding and generating aroma compounds, respectively. A total of 13 lipids were determined as potential markers for the discrimination among RDM and CDM, including PC(O-16:2/2:0), LPE(22:5/0:0), and PC(P-16:0/2:0). In conclusion, this study provided useful information about the metabolic and lipid profiles of donkey meat which may explain its unique taste and flavor, which could serve as a basis for the development and quality control of donkey meat and its products.